Clinical features of adenosine sensitive syncope and tilt induced vasovagal syncope. Issue 1 (1st January 2000) - Brignole, M; Gaggioli, G; Menozzi, C; Del Rosso, A; Costa, S; Bartoletti, A; Bottoni, N; Lolli, G
Abstract : AIM: To evaluate the possible relation between adenosine sensitive syncope and tilt induced vasovagal syncope. METHODS: An ATP test and a head up tilt test were performed in 175 consecutive patients with syncope of uncertain origin. The ATP test consisted of the rapid intravenous injection of 20 mg of ATP; a positive response was defined as the induction of a ventricular pause (maximum RR interval) ⩾ 6000 ms. The head up tilt test was performed at 60° for 45 minutes; if negative, 0.4 mg oral glyceryl trinitrate spray was given and the test continued for a further 20 minutes; a positive response was defined as induction of syncope in the presence of bradycardia, hypotension, or both. RESULTS: Of the 121 patients with a positive response, 77 (64%) had a positive head up tilt alone, 18 (15%) had a positive ATP test alone, and in 26 (21%) both ATP and head up tilt were positive. Compared with the patients with isolated positive head up tilt, those with isolated positive ATP were older (mean (SD) age, 68 (10) v 45 (20) years), had a lower median number of syncopal episodes (2 v 3), a shorter median duration of syncopal episodes (4 v 36 months), a lower prevalence of situational, vasovagal, or triggering factors (11% v 64%), a lower prevalence of warning symptoms (44% v 71%), and a higher prevalence of systemic hypertension (22% v 5%) and ECG abnormalities (28% v 9%). The patients with a positive response to both tests had intermediate features. Of the 44 positive responses to the ATP test, atrioventricular block was the cause of the ventricular pause in 43; of the 29 positive cardioinhibitory responses to head up tilt, sinus arrest was present in 23 cases and atrioventricular block in six. CONCLUSIONS: ATP and head up tilt tests identify different populations of patients affected by syncope; these have different general clinical features, different histories of syncopal episodes, and different mechanism sites of action. Therefore, adenosine sensitive syncope and tilt induced vasovagal syncope are two distinct clinical entities.